Management and Prevention of Herpes Zoster in the Immunocompromised Inflammatory Bowel Disease Patient: A Clinical Quandary. Issue 10 (October 2016) - Côté-Daigneault, Justin; Peerani, Farhad; MacMahon, Eithne; Delaporte, Emmanuel; Rahier, Jean-François; Colombel, Jean-Frédéric
Abstract : Abstract: Crohn's disease (CD) and ulcerative colitis (UC), the 2 main clinical phenotypes of inflammatory bowel disease (IBD), are diseases that result from a dysregulated immune response to gut microbiota in genetically susceptible hosts. This aberrant immune response may intrinsically predispose IBD patients to infectious complications. Moreover, immunosuppressive medications used to treat IBD including corticosteroids, thiopurines, methotrexate, calcineurin inhibitors, anti-tumor necrosis factor (anti-TNF) agents and other biologics, further increase patients' susceptibility to opportunistic infections. Herpes zoster (HZ), also known as shingles, is an opportunistic viral reactivation often observed in IBD patients with several case reports demonstrating complicated or disseminated disease in those on immunosuppression. While HZ vaccination is recommended in all immunocompetent adults aged ≥60 years, as a live virus vaccine, it is currently contraindicated in IBD patients on anti-TNF therapy and in other significantly immunocompromised patient groups. While caution is still warranted in these circumstances, recent clinical data has emerged which has prompted us to review and examine the universal approach to HZ vaccination in the immunosuppressed IBD population. In the following narrative review, we will discuss and provide an overview of the clinical manifestations, incidence, management and prevention of HZ in the IBD patient.